(untitled) (Jurnal Arsitektur ARCADE, 2026)
This study aims to identify and classify spatial transformations in the traditional houses of Kampung Naga, Tasikmalaya, by comparing floor plans before and after modification. These houses represent vernacular architecture reflecting Sundanese cultural values and social structures. Utilizing a mixed-method approach, the research analyzes six case studies: one original baseline typology and five modified houses (P1–P5). Data was gathered through field observations, measurements, interviews, and visual documentation to reconstruct original layouts. The analysis evaluates spatial configuration, room functions, circulation, and proportions, calculating the percentage of retained versus altered spaces. Results indicate that the original spatial organization follows a linear, hierarchical pattern consisting of the golodog, pawon, bedroom, and goah. Transformations are classified into three levels: Minor change (≥75% authenticity), Moderate change (50–74%), Major change (≤49%) The findings reveal that higher levels of modification directly correlate with decreased spatial authenticity and integrity. Consequently, an adaptive conservation approach—grounded in principles of authenticity and reversibility—is essential to preserve the spatial identity of Kampung Naga while accommodating contemporary living needs.